2002
DOI: 10.1021/ja026422l
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Symmetry Breaking in Cofacial and Linear Dimers of a Green Perylenediimide Chlorophyll Analogue Leading to Ultrafast Charge Separation

Abstract: Photoexcitation of chromophoric dimers constrained to a symmetric pi-stacked geometry by their molecular structure usually produces excimers independent of solvent polarity, while dimers with edge-to-edge perpendicular pi systems undergo excited-state symmetry breaking in highly polar solvents leading to intradimer charge separation. We present direct evidence for symmetry breaking in the lowest excited singlet state of a symmetric cofacial dimer of 1,7-bis(pyrrolidin-1'-yl)-perylene-3,4:9,10-bis(dicarboximide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
282
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(296 citation statements)
references
References 16 publications
13
282
1
Order By: Relevance
“…Although some of the materials are self-organized through chemical interactions to produce larger scale arrays, others are organized on surfaces by using techniques such as Langmuir-Blodgett films or synthesized by assembling encapsulated materials into or onto host-guest inorganic matrices. Wasielewski et al (47,84) recently reported that xanthene-linked green chromophores tetrafunctionalized with perylene-bis(dicarboximide) were highly efficient at both light harvesting and ultrafast charge separation. The researchers attributed this efficiency to the molecules' ability to self-assemble into stacked arrays with defined orientations between adjacent planar aromatic groups (47,84).…”
Section: Opportunities For Nanotechnology: Synthetic and Biomimetic Amentioning
confidence: 99%
See 1 more Smart Citation
“…Although some of the materials are self-organized through chemical interactions to produce larger scale arrays, others are organized on surfaces by using techniques such as Langmuir-Blodgett films or synthesized by assembling encapsulated materials into or onto host-guest inorganic matrices. Wasielewski et al (47,84) recently reported that xanthene-linked green chromophores tetrafunctionalized with perylene-bis(dicarboximide) were highly efficient at both light harvesting and ultrafast charge separation. The researchers attributed this efficiency to the molecules' ability to self-assemble into stacked arrays with defined orientations between adjacent planar aromatic groups (47,84).…”
Section: Opportunities For Nanotechnology: Synthetic and Biomimetic Amentioning
confidence: 99%
“…Wasielewski et al (47,84) recently reported that xanthene-linked green chromophores tetrafunctionalized with perylene-bis(dicarboximide) were highly efficient at both light harvesting and ultrafast charge separation. The researchers attributed this efficiency to the molecules' ability to self-assemble into stacked arrays with defined orientations between adjacent planar aromatic groups (47,84). Self-assembled monolayers of carotenoids and chlorophylls on titania surfaces showed long-lived photoinduced charge separation due to a reductive quenching of the pheophytin molecules upon pheopytin excitation at 670 nm (81).…”
Section: Opportunities For Nanotechnology: Synthetic and Biomimetic Amentioning
confidence: 99%
“…The fact that the behavior observed is identical for the two geometries shown above indicates that effect is not likely due to field-induced charge carrier generation and separation as is often described in similar experiments. 4 To further explore the origins of this effect, we have also performed power-dependent and field-dependent studies. Figure 11 shows the relative fluorescence signal (field on relative to field off) to be independent of incident power, indicating these effects do not arise from any nonlinear photoinduced processes.…”
Section: Electric-field-induced Fluorescence Quenching Studiesmentioning
confidence: 99%
“…tension of the air-water interface from 71.0 mN/m to 65. 4 X-ray scattering data obtained in studies of the C 12 -mN/m at a concentration of 100/uM, as determined by the PDI+/PA-composite thin films are shown in Figure 2. capillary rise method.…”
Section: 6007mentioning
confidence: 99%
See 1 more Smart Citation